Development of an arterio-venous difference method to study the metabolic physiology of the femoral adipose tissue depot. - McQuaid, SE; Manolopoulos, K; Dennis, A; Cheeseman, J; Karpe, F; Frayn, K (2010)
Gluteofemoral adipose tissue (AT) has interesting positive associations with metabolic health, yet little is known of its metabolic physiology. Here, we describe a technique for cannulation of a vein draining the femoral fat depot. Using ultrasound guidance, a cannula was introduced into a superficial branch of the great saphenous vein. We also obtained arterialized blood and, for comparison, blood representing drainage from forearm muscle and from subcutaneous abdominal AT. We measured appropriate biomarkers of skeletal muscle (creatinine) and AT (nonesterified fatty acids (NEFAs), glycerol, leptin) drainage. Blood obtained in this way from the saphenous vein did not show creatinine release (creatinine concentration 100.5 +/- 0.4%, mean +/- s.e.m., of that in arterialized blood), whereas creatinine concentrations in blood draining forearm muscle averaged 121 +/- 1% of those in arterialized blood. Fatty acid release from the tissue drained was suppressed after feeding and increased during beta-adrenergic stimulation. We also demonstrated leptin secretion. These findings suggest that blood so obtained is representative of AT drainage with little apparent contribution of skeletal muscle. We believe this technique will facilitate physiological studies of a lower-body fat depot in humans.